2023
DOI: 10.1371/journal.pone.0272952
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in motor and non-motor symptoms in individuals with mild-moderate Parkinson’s disease

Abstract: Background Parkinson’s disease (PD) affects both men and women with documented gender differences across functional domains, with findings varying among reports. Knowledge regarding gender differences in PD for different geographic locations is important for further understanding of the disease and for developing personalized gender-specific PD assessment tools and therapies. Objective This study aimed to examine gender differences in PD-related motor, motor-cognitive, cognitive, and psychosocial function in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…Noteworthy, the study by Solla and colleagues showed that female sex was a clinical variable predicting the presence of OHs in PD patients [40]. These data reinforced the putative central role of sex differences in the development of NMSs in PD patients, with particular references to olfactory symptoms [55][56][57]. Future research on phantosmia should explore the potential influence of sex on the development of OHs in PD patients.…”
Section: Discussionmentioning
confidence: 86%
“…Noteworthy, the study by Solla and colleagues showed that female sex was a clinical variable predicting the presence of OHs in PD patients [40]. These data reinforced the putative central role of sex differences in the development of NMSs in PD patients, with particular references to olfactory symptoms [55][56][57]. Future research on phantosmia should explore the potential influence of sex on the development of OHs in PD patients.…”
Section: Discussionmentioning
confidence: 86%
“…Nevertheless, no significant effect of sex on PD-like phenotypes in mice contrasts with some other observations from studies on male and female PD patients cohorts ( Picillo et al, 2016 ; Perrin et al, 2017 ; Li et al, 2023 ). Some reports indicate that male PD patients experience greater decline of motor and non-motor function, though no sex-dependent differences in progression rate were found ( Abraham et al, 2019 , 2023 ; Picillo et al, 2022 ; Li et al, 2023 ).…”
Section: Discussionmentioning
confidence: 98%
“…Marginal effects of disease duration on the outcomes (i.e., disease duration averaged over random-effects) of the outcomes were estimated with the function "ggpredict" of the R package ggeffects 27 to describe the progression in both groups, illustrated as a plot with the function "plot_model" of the R package sjPlot 28 . As women's ratings of disability differed between self-reported and physician-reported 29 , we categorised the results in patient-reported or clinician-assessed outcomes / performance tests. Time, in this case modelled as disease duration, was included in the mixed models to describe progression of the different outcomes (significance tested via t-test).…”
Section: Methodsmentioning
confidence: 99%